If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x = 3y(y + w) + -1 Reorder the terms: x = 3y(w + y) + -1 x = (w * 3y + y * 3y) + -1 x = (3wy + 3y2) + -1 Reorder the terms: x = -1 + 3wy + 3y2 Solving x = -1 + 3wy + 3y2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Simplifying x = -1 + 3wy + 3y2
| k=5/8m | | 4x-9+2x=-6x+5 | | 6(3x+2)+5(7x-6)-12x=6(x-3)+5(6x-1) | | X^2-8x=100 | | 7xy+2y^2=1 | | 20y^4+35y^3+15y^2= | | 78-u=271 | | -1(t^2-3t-10)=0 | | -1=5-2x/3 | | x-23=x+77 | | -98/-18 | | (-8-90)/2(-8)-2 | | (-8-90)/2x(-8)-2 | | 4m^2-36mn+81n^2= | | x+4.9=6.89 | | 2.6x-52=1.3x | | 2.6x-52=1.3 | | 5x-27=x+30 | | 8ab^2-12a^2b= | | 2(y+x)=-(-3x+10) | | 29-35=-5 | | 8x-20=2x+40 | | 4x-7=-x-9 | | a^2+11=3a | | x^2+y^2+16x-12y+10=0 | | x^2+20x-74=8x-10 | | 3x^2-5-4x=10x+65-3x | | 6x+1=-0.4x-2 | | (x+y)(x+2y)= | | 3(2-x)-2(2x+1)=3 | | 6x+1=0.4x+2 | | 2-3(4x)=5(2-x)+4x |